PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN (Studi Kasus Peacockoffie Gombel Semarang) - Shania Aulia Rahma; Agus Hermani Daryanto Seno (Jurnal Ilmu Administrasi Bisnis, 2022)
Abstract: A lot of coffee shop in  Semarang makes shop owners compete to win the competition. One way is to have a high level of consumer loyalty. High consumer loyalty can be influenced by the good product quality and low prices. In fact, not all coffee shops have high loyalty, including Peacockoffie Gombel. This study aims to determine the effect of product quality and price on consumer loyalty Peacockoffie Gombel. This type of research is explanatory research with a purposive sampling method. Data collection techniques were used by distributing questionnaires and interviewing 100 respondents who have made purchases at Peacockoffie Gombel at least 3 times. The data analysis method used is regression analysis using the SPSS 26.0 application. The results of this study indicate that product quality affects consumer loyalty and prices that affect consumer loyalty, and there is an influence between product quality and price on consumer loyalty. The suggestions given to Peacockoffie Gombel on product quality aspects need to be improved, especially in terms of menu diversity, appearance in the presentation of drinks and food, as well as the distinctive taste and aroma of drinks and food to be able to satisfy consumer desires with an appetizing taste and appearance. In terms of price, it is necessary to vary the price to be able to compete with other coffee shops. Meanwhile, from the aspect of consumer loyalty, there needs to be a promotion in the form of a bundling package so that consumers can try other product variants without having to spend more money, or by presenting a unique name on the menu variant to attract consumers.